ANALISIS SISTEM PENCATATAN PENERIMAAN DAN PENGELUARAN KAS PADA ASTRA CREDIT COMPANIES CABANG CIDENG JAKARTA - Asmonah, Siti; Budi, Saksono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to analyze cash receipts and disbursements at Astra Credit Companies. The method used is a case study by conducting observations, interviews, and analyzing documents related to cash receipts and disbursements. The results showed that the main source of cash receipts of Astra Credit Companies Cideng Branch came from credit installment payments. Meanwhile, the largest cash expenditure of Astra Credit Companies Cideng Branch is for the purchase of Office needs, stationery and Entertain Client payments. Although there are some shortcomings in cash management, the Astra Credit Companies Cideng Branch has managed to maintain a good financial balance. This research recommends that Astra Credit Companies Cideng Branch continues to improve the accounting system and manage cash expenditure effectively to ensure the company's finances are well organized.